Development of an Index Questionnaire for the Degree of Teenagers' Sexual Risk Behavior - Erni Chaerani; Erlinda Widyaastuti, Eny (KHD-Production, 2024)
The adolescent phase is a crucial period in terms of growth and development, making it essential to have a specialized tool that accurately measures adolescent sexual behavior levels. Such an instrument could serve as an initial screening tool to identify potential deviations or to monitor healthy development during adolescence. This study aimed to assess the validity and reliability of the Adolescent Sexual Behavior Degree Index. Research was conducted in high schools across three districts on Bangka Island, involving 348 adolescent participants. Findings indicated that format 2 had an r-count value for each questionnaire item exceeding the r-table threshold, confirming its validity. This conclusion was based on a decision criterion where the r-count (Pearson Product Moment Correlation) exceeded the r-table value of 0.4438 at df = 18 with α = 0.05, deeming the instrument valid. In the second stage, reliability testing of the Adolescent Sexual Behavior Degree Index showed an r-count greater than the critical r value, with a Cronbach's Alpha of 0.979. These results confirm that the 20 questions in the Index are statistically reliable, as indicated by the high reliability coefficient of 0.979, well above the threshold of 0.6.